Effect of TO901317 on GF to promote the differentiation of human bone marrow mesenchymal stem cells into dopamine neurons on Parkinson's disease. (March 2021) - Li, Miaomiao; Yang, Junqing; Cheng, Oumei; Peng, Zhe; Luo, Yin; Ran, Dongzhi; Yang, Yang; Xiang, Pu; Huang, Haifeng; Tan, Xiaodan; Wang, Hong
Background: Human bone marrow mesenchymal stem cells (hBMSCs) could differentiate into dopamine-producing cells and ameliorate behavioral deficits in Parkinson's disease (PD) models. Liver X receptors (LXRs) are involved in the maintenance of the normal function of central nervous system myelin. Therefore, the previous work of our team has found the induction of cocktail-induced to dopaminergic (DA) phenotypes from adult rat BMSCs by using sonic hedgehog (SHH), fibroblast growth factor 8 (FGF8), basic fibroblast growth factor (bFGF), and TO901317 (an agonist of LXRs) with 87.42% of efficiency in a 6-day induction period. But we did not verify whether the induced cells had the corresponding neural function. Methods: Expressions of LXRα, LXRβ, and tyrosine hydroxylase (TH) were detected by immunofluorescence and western blot. Adenosine triphosphate-binding cassette transporter A1 (ABCA1) was detected by quantitative real-time PCR. The induced cells were transplanted into PD rats to study whether the induced cells are working. Results: The induced cells can release the dopamine transmitter; the maximum induction efficiency of differentiation of hBMSCs into DA neurons was 91.67% under conditions of combined use with TO901317 and growth factors (GF). When the induced-cells were transplanted into PD rats, the expression of TH in the striatum increased significantly, and the behavior of PD rats induced by apomorphine was significantly improved. Conclusion: The induced cells have the function of DA neurons and have the potential to treat PD. TO901317 promoted differentiation of hBMSCs into DA neurons, which may be related to activation of the LXR-ABCA1 signaling pathway.